Sources and effectiveness of financial development: What we know and what we need to know - Panicos O. Demetriades; Svetlana Andrianova (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2005)
Drawing on recent literature, the paper argues that institutions and political economy factors hold the key to understanding why some countries have succeeded in developing their financial systems while others have not. The paper also reviews new evidence which suggests that institutional quality may influence the effectiveness of financial development in delivering economic growth. These new findings highlight the possibility that poor countries may be stuck in a bad equilibrium, in which weak institutions inhibit growth both directly and indirectly, through under-developed, low-quality finance. In addition, the paper identifies a number of unanswered questions in the financial development literature, including the precise role of important institutions like law in finance, and the influence of geographical factors.
Keywords: O16; 330; financial development; growth; institutions; banking; Finanzsektor; Kapitalmarktliberalisierung; Bankenpolitik; Privatisierung